The larvicidal activity of auraptene: oxygeranylated coumarin from Limonia acidissima L. - Siti Mariyatul Ulfah; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung; Ratih Dewi Saputri; Eva Marliana (Acta Chimica Asiana, 2026)
Limonia acidissima  L. (Rutaceae) is a plant rich in coumarin compounds and has been used in traditional medicine. One of the main coumarin compounds reported from the roots of this plant is auraptene (7-oxygeranylcoumarin), which has previously been reported to have antioxidant activity. With increasing cases of vector-borne diseases, especially dengue fever transmitted by Aedes aegypti, the development of effective and environmentally friendly natural larvicides is needed. This study aimed to evaluate the larvicide activity of auraptene, building on previous research. The larvicide test was carried out using the WHO larval bioassay method on third-instar A. aegypti larvae at concentrations of 25–500 ppm within an exposure time of 24 h. Mortality data were analyzed using probit analysis to determine the Lethal Concentration 50% (LC50) value. The results showed that auraptene increased larval mortality with an LC50 of 145.29 ± 0.02 ppm after 24 h of exposure. This value indicates that auraptene is classified as an active natural larvicide. In conclusion, auraptene has the potential to be developed as a natural larvicidal candidate against A. aegypti and may expand the spectrum of biological activity of coumarin compounds from L. acidissima L.